Pre-service teachers evaluating online texts about learning styles: there is room for improvement in justifying the credibility - Kulju, Pirjo; Hämäläinen, Elina K.; Mäkinen, Marita; Räikkönen, Eija; Kiili, Carita (Frontiers in Education, 2024)
Teachers' abilities to critically evaluate the credibility of online information are fundamental when they educate critical online readers. This study examined pre-service teachers' abilities to evaluate and justify the credibility of online texts on learning styles. Pre-service teachers (N = 169) read and evaluated two more and two less credible online texts on learning styles in a web-based environment. Most pre-service teachers were able to differentiate the more credible texts from the less credible ones but struggled with justifying the credibility. Pre-service teachers' inaccurate prior beliefs about learning styles impeded questioning the less credible texts. Implications for teacher education are discussed.